Rekayasa Perangkat Lunak Aplikasi Pemilahan Sampah Berbasis Web Menggunakan Metode Waterfall - Nandya Hajar Azzulfa (Masoem University, 2026)
Household waste management requires an integrated information system to improve the effectiveness of waste sorting, collection scheduling, and reporting activities. At Perum Griya Surya Indah, waste management activities were still conducted manually, resulting in recording errors, delays in information delivery, and difficulties in preparing reports. This study aimed to develop a web-based waste sorting application capable of integrating waste sorting, collection scheduling, and reporting processes into a single platform. The software was developed using the Waterfall method, which consists of requirements analysis, design, development, testing, and maintenance stages. Data were collected through observation, interviews, and literature studies. The results showed that the developed application was able to manage user data, waste sorting records, collection schedules, and reports in an integrated manner. Functional testing indicated that all system features operated according to user requirements. The implementation of the system improved data accuracy, operational efficiency, and monitoring activities in residential waste management. Therefore, the Waterfall method remained suitable for developing structured web-based information systems.